SIMBOL-SIMBOL BUDAYA DAN RELIGI DALAM FILM ADA SURGA DI RUMAHMU - Fitriansyah Hidayat; Rudy Suryana (STKIP Paris Barantai, 2017)
This study aims to determine the cultural symbols contained in the movie There is Heaven in your House and know the religious symbol contained in the film There Heaven in Rumahmu.Metode used in this study is descriptive qualitative method that describes objectively the state of the data source reviewed . From the results of this study indicate that (1) Cultural symbol used by the author consists of several, namely songket, lakso (laksa), language, pempek Palembang, ampera bridge and musi river and raft house. (2) The religion used by the author consists of four aspects namely the dimension of the creed (ideology) which consists of faith in God, faith in qadha and qadhar. Dimension of worship (ritual) which consists of special worship, public worship. Dimension ihsan (appreciation), and dimension of knowledge (knowledge). (3) Factors that can affect religiosity are divided into two: a) the influence of education or teaching and various social pressures (social factors) consisting of parental education, as well as pressure from the social environment b) experience factor. Keywords: Symbols, Culture, Religion, Film